Garra waensis, a new cyprinid fish (Actinopterygii: Cypriniformes) from the Nan River basin of the Chao Phraya River system, northern Thailand - Lothongkham, Amornchai; Arbsuwan, Sakda; Musikasinthorn, Prachya (Zootaxa, 2014)
A new cyprinid fish, Garra waensis, is described from the Wa River, a tributary of the Nan River of the Chao Phraya River system in northern Thailand. The species is distinguishable from its congeners by the combination of the following characters: the absence of barbels; 7 branched dorsal fin rays; 31–37 lateral-line scales; 10–12 circumpeduncular scales; a small and broad head (head length [HL] 22.7–26.1% in standard length, head depth 56.1–64.9% HL, head width 74.0–85.0 % HL); a weakly developed proboscis in front of nostrils; the presence of reddish-orange spots (white or dull yellowish white in preserved specimens) on the side of the body; and a dark mid-lateral stripe running from the upper edge of the gill opening to the caudal peduncle and expanding into a large anteriorly-pointed triangular blotch at the end of the body (in preserved condition). A vomero-palatine organ of the species is also described in detail for the first time for Asian species of Garra. The genus Placocheilus is treated as a junior synonym of Garra.